A suggested algorithm for detection of multi drug-resistant tuberculosis in Zimbabwe: MDR-TB detection in resource limited settings - Makamure, Beauty; Makumbirofa, Salome; Bandason, Tsitsi; Leccese, Paul; Mutetwa, Reggie; Robertson, Val; Mason, Peter (The Journal of Infection in Developing Countries, 2017)
Introduction: Rapid genotypic and phenotypic methods for multi-drug-resistant-tuberculosis (MDR-TB) detection are now widely available. Zimbabwe adopted the use of GeneXpert-MTB/RIF, microscopic-observation-drug-susceptibility-assay (MODS) and Mycobacteria-Growth-Indicator-Tube (MGIT) drug-susceptibility-testing (DST). Data is limited on the ideal combination of use of these methods in resource limited settings. Methodology: Between August 2014 to July 2015, 211 sputa from MDR-TB suspects were tested with GeneXpert-MTB/RIF, MODS, manual-MGIT and Lowenstein-Jensen (LJ)-DST to determine diagnostic accuracy and turnaround-time (TAT), with LJ-DST as the gold standard. A performance score ranking table for diagnostic accuracy, TAT, costs, facilities and expertise requirements, was used to determine the most favourable tool. Results: GeneXpert-MTB/RIF sensitivity was 96% (95%CI:80-100) and specificity was 95% (95%CI:90-97). MODS sensitivity was 88% (95%CI:68-97) and specificity was 97% (95%CI:87-100). Manual MGIT-DST had slightly lower sensitivity of 80% (95%CI:59-93). Median time to detection of MDR-TB was <1 day (IQR:0-0) for Xpert, 14 days (IQR:11-31) for MODS, 21 days (IQR:7-22) for MGIT-DST and 28 days (IQR:25-28) for LJ-DST. Operational costs for MODS, MGIT-DST, and GeneXpert-MTB/RIF were $21.20, $27.52 and $39.76 respectively. From a summation of scores including facility and expertise requirements per diagnostic technique, GeneXpert-MTB/RIF was the most favourable tool, followed by MODS and MGIT-DST. Conclusions: For best scale-up of MDR-TB diagnosis in Zimbabwe, GeneXpert-MTB/RIF can be used for rapid detection of TB in smear negative cases, RIF-susceptibility for early treatment initiation and probable MDR-TB. MODS can rapidly confirm probable MDR-TB detected by GeneXpert-MTB/RIF, manual-MGIT can provide early results for susceptibility to other antibiotics, with affordable costs, with LJ-DST confirming discordant DSTs.